1975
DOI: 10.1001/jama.232.12.1243
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive airway diseases. Current concepts in diagnosis and comprehensive care

Abstract: Physicians and paramedical personnel often find the early diagnosis and differentiation of obstructive airway diseases to be a challenging problem. The history and physical examination are often not enough to allow the physician to detect either the presence of, or determine the type of, disease present. Patterns of pulmonary function abnormality to determine the presence of obstructive or restrictive defects are discussed. Guidelines useful in the differentiation of obstructive airway diseases are presented. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
2

Year Published

1976
1976
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 96 publications
0
10
0
2
Order By: Relevance
“…Chronic airway obstruction is one of the most relevant health problems in industrial world [5,11,12,21]. The real efficacy of the therapeutical measures usually em ployed is still discussed [6,14,19,24], The studies reporting the clinical effect of 'com prehensive' programs of treatment including medical therapy and respiratory rehabilita tion techniques have given different results [9, 10,17,18,20].…”
mentioning
confidence: 99%
“…Chronic airway obstruction is one of the most relevant health problems in industrial world [5,11,12,21]. The real efficacy of the therapeutical measures usually em ployed is still discussed [6,14,19,24], The studies reporting the clinical effect of 'com prehensive' programs of treatment including medical therapy and respiratory rehabilita tion techniques have given different results [9, 10,17,18,20].…”
mentioning
confidence: 99%
“…With this information the patient felt assured that "hypnosis worked." ACOSTA-AUSTAN Conclusion Medical investigators have reported that patients with COPD have a reduction in thoracic and diaphragmatic motion which is often compromised further during periods of anxiety (Hodgkin et al, 1975;Faulkner, 1941). The consequence of this action exacerbates the existing work of breathing and creates a sense of suffocation.…”
Section: Resultsmentioning
confidence: 99%
“…Respiratory disorders that may precipitate acute respiratory failure and the subsequent need for mechanical ventilation support include COPD, pneumonia, asthma, bronchitis, bronchiolitis, and emphysema (Hodgkin et al, 1975;Lightowler, Wedzicha, Elliott, & Ram, 2003). Although psychological factors have been implicated in ventilator weaning success based on clinical observations, there has been very limited study.…”
Section: Mechanical Ventilator Supportmentioning
confidence: 99%
“…There is long-standing recognition, based on clinical observation and limited empirical work, that patients with chronic respiratory disorders (e.g., emphysema, asthma, chronic bronchitis) experience significant distress in association with dyspnea (Hodgkin et al, 1975). Indeed, guidelines for the comprehensive treatment of chronic obstructive airway disorders, published more than 25 years ago, included recommendations for relaxation exercises (Hodgkin et al, 1975).…”
mentioning
confidence: 99%
See 1 more Smart Citation